Business Source Ultimate.
Economische databank met heel wat artikels over economie, financiën, marketing, het zakenleven…// Business Source Ultimate provides access to over 3,500 full text journals, industry and company profiles, trade publications, case studies and SWOT analyses.
Keywords: Bedrijfsmanagement; Tijdschriftartikels; Toerisme